Asynchrony of directional auditory warnings and visual information in hands-on SAE level 2 automated vehicles: Analysis of driver responses - Ali Arabian; Courtney M. Goodridge; Natasha Merat (PLoS ONE, 2025)
As automated driving technology advances, the development of an efficient human-machine interface (HMI) for delivering hazard warnings becomes increasingly critical for maintaining driving safety. One example is the use of directional auditory warnings in vehicles, which are used to direct drivers’ attention, either towards a free lane to move into, or towards the location of hazards. These warnings have the potential to reduce the time it takes for drivers to take over from automation, improving overall takeover quality. Findings from lab-based studies have shown that the timing of directional auditory warnings, particularly in relation to accompanying visual cues, plays a crucial role in how effectively they are processed. Specifically, asynchrony between auditory stimuli and visual information, known as stimulus onset asynchrony (SOA), may enhance the effectiveness of auditory warnings by reducing reaction times. However, the impact of such temporal separation in real-world settings, especially during the transitions of vehicle control, is still unknown. Drivers (N = 48) were recruited for an experiment investigating how directional auditory warnings and asynchronous presentation of auditory warnings and visual information affect takeover performance from a hands-on SAE L2 automated vehicle. Results showed that directional auditory warnings reduced first steering reaction times, enhanced the accuracy of the first steering response, and resulted in smaller maximum lateral acceleration, relative to non-directional warnings. Notably, warnings that indicated the location of a free lane, and therefore a safe direction for drivers to steer towards for avoiding an obstacle, were associated with improved takeover performance and lower subjective workload. Additionally, longer SOAs were associated with reduced dominance of visual information, resulting in faster first steering response times and slight improvements in takeover quality. These findings provide evidence that directional warnings can facilitate faster and higher-quality takeover performance. Furthermore, attenuation of the visual dominance effect provides insight into how the temporal separation of auditory and visual components of audiovisual directional warnings may facilitate improved takeover performance.